Starch-based hard carbon material, preparation thereof and application of starch-based hard carbon material in sodium-ion battery
Through the method of atmospheric-high pressure heat treatment and additive modification combined with low-temperature carbonization, the problem of poor performance stability of starch-based hard carbon materials in sodium ion batteries was solved, and a starch-based hard carbon material with excellent capacity and fast charging performance was prepared. Carbon material, suitable for sodium ion battery negative electrode material.
Patent Information
- Application Number
- CN202411288273.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-14
- Publication Date
- 2025-01-03
- Estimated Expiration
- 2044-09-14
AI Technical Summary
During the preparation process, existing starch-based hard carbon materials have problems such as difficult performance, easy foaming and high-temperature treatment, which leads to poor performance stability and difficult to achieve excellent capacity, high energy density and fast charging stability in sodium ion batteries. sex.
The starch-based hard carbon material is prepared by using the method of atmospheric-high pressure two-stage heat treatment and additive modification combined with low-temperature carbonization. The first phase of atmospheric heat treatment and the second phase of high-pressure heat treatment, followed by the low temperature of 750℃~950℃ Carbonization is carried out to optimize the material's physical and chemical structure, and improve its capacity, density and fast charging performance.
The starch-based hard carbon material with excellent capacity, high energy density and high rate fast charging stability was successfully prepared at low temperature, which solved the problem of easy foaming of starch raw materials and poor performance stability, and realized the sodium ion battery. High performance applications.
Smart Images

Figure CN119240656A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of electrochemical energy storage battery materials, and in particular to a negative electrode carbon material for a sodium ion battery and a preparation method thereof. Background Art
[0002] With the continuous consumption of non-renewable energy, the development and utilization of clean renewable energy is an effective way to achieve the transformation of energy structure. However, due to the random and volatile characteristics of renewable energy such as wind and solar energy, energy storage devices are required in practical applications to overcome the temporal limitations of renewable energy. Lithium-ion batteries are currently the most widely used electrochemical energy storage devices. However, due to the low abundance of lithium in the earth's crust and its uneven geographical distribution, limited lithium resources cannot meet the rapid growth of lithium-ion battery market demand. Sodium-ion batteries have become an excellent alternative to lithium-ion batteries because of their similar physical and chemical properties, lower cost, and higher safety.
[0003] In sodium-ion batteries, negative electrode carbon materials are one of the most widely studied sodium-ion negative electrode materials, and are also the most promising materials. Among them, hard carbon materials are particularly popular. Hard carbon is a carbon material that is difficult to graphitize even at high temperatures. Its structure can be expressed by the classic "house of cards" model structure. Hard carbon is composed of randomly distributed graphite nano-regions, curled graphene nano-sheets, and microporous structures. It has a good sodium-ion battery capacity due to its porous and messy structure. The range of hard carbon precursors is very wide. Coal, bark, rice husks, starch, etc. can all be used as raw materials for hard carbon materials, which are low-cost and environmentally friendly. The preparation process of hard carbon materials includes pretreatment, precarbonization and carbonization. Some of the precursors require chemicals (HNO3, NH4(HPO3)2, etc.) in the pretreatment, which may be harmful and polluting; some precarbonization is carried out in an argon-protected tubular furnace at 300℃~400℃, which will consume more argon; the carbonization temperature of hard carbon is generally between 1000℃~1600℃, which requires more electricity consumption and longer process time. Summary of the invention
[0004] In response to the problems faced by existing starch-based hard carbon materials, the first purpose of the present invention is to provide a method for preparing starch-based hard carbon materials, aiming to prepare hard carbon materials with excellent capacity, high energy density and high-rate fast charging stability.
[0005] The second purpose of the present invention is to provide a powder-based hard carbon material obtained by the preparation method and its application in sodium ion batteries.
[0006] The third object of the present invention is to provide a sodium ion battery comprising the starch-based hard carbon material and its negative electrode and negative electrode material.
[0007] Starch is one of the main raw materials for preparing hard carbon, but it is easy to foam and its performance is difficult to control. In addition, in order to obtain ideal disorder and electrochemical performance, it is basically necessary to prepare it at a temperature above 1000°C. In view of this problem, the present invention provides the following improvement scheme:
[0008] A method for preparing a starch-based hard carbon material, comprising the steps of:
[0009] Step 1:
[0010] The aqueous solution containing starch raw material is preliminarily subjected to a first stage of normal pressure heat treatment, and then subjected to a second stage of high pressure heat treatment in a closed container, and then separated to obtain material A; the temperature of the first stage of normal pressure heat treatment is above 50°C; the temperature of the second stage of high pressure heat treatment is above 100°C;
[0011] Step 2:
[0012] Material A and an auxiliary agent are slurried and modified with water to obtain material B; the auxiliary agent is an alkaline component or an acidic component;
[0013] Step 3:
[0014] Material B is subjected to low-temperature carbonization at a temperature of 750° C. to 950° C. to obtain the starch-based hard carbon material.
[0015] In order to solve the problems of unsatisfactory performance and stability of hard carbon products caused by easy foaming of starch raw materials, the present invention innovatively subjects the starch raw materials to the two-stage heat treatment of normal pressure and high pressure, and further cooperates with subsequent auxiliary agent modification and low-temperature carbonization treatment, so as to realize the preparation of starch-based hard carbon at low temperature. Not only that, it can also optimize its physical and chemical structure, improve its capacity, tap density, fast charging and high-rate stability.
[0016] In the present invention, the starch raw material can be any starch-containing raw material in the industry, for example, it can be at least one of wheat starch, corn starch, and potato starch.
[0017] In the present invention, the starch raw material is dispersed in water and mixed to obtain the aqueous solution containing the starch raw material.
[0018] Preferably, the starch raw material is pre-dispersed in solution A and then dispersed in water to obtain the aqueous solution containing the starch raw material; the solution A is an aqueous solution in which at least one solute selected from calcium chloride, an organic acid, chloroformaldehyde, and an alkali is dissolved. The organic acid is, for example, at least one selected from acetic acid, malic acid, citric acid, oxalic acid, and the like.
[0019] In the present invention, the starch raw material is innovatively pre-dispersed in solution A and then dispersed in water, and further combined with subsequent treatments such as normal pressure and high pressure, the physical and chemical structure of the hard carbon material can be further strengthened, and a starch-based hard carbon material with better fast charging and stability can be obtained.
[0020] In the present invention, the concentration of the solute in the solution A is 1-5M, and can further be 3-4M.
[0021] In the present invention, in the aqueous solution containing the starch raw material, the liquid-to-solid ratio of water to the starch raw material is 5 to 50 ml / g.
[0022] In the present invention, the first stage of normal pressure heat treatment is carried out in an open container.
[0023] In the present invention, the atmosphere of the first stage normal pressure heat treatment is air.
[0024] In the present invention, the temperature of the first stage normal pressure heat treatment is 50 to 90°C, and can further be 70 to 90°C.
[0025] In the present invention, the time of the first stage of normal pressure heat treatment is 0.5 to 1 hour.
[0026] In the present invention, the system of the first stage of normal pressure heat treatment is placed in a sealed container and heated for the second stage of high pressure heat treatment. In the present invention, the high pressure heat treatment refers to the pressure of the sealed system at the system (P = nRT / V).
[0027] In the present invention, the temperature of the second stage high pressure heat treatment is 150°C to 250°C, preferably 190°C to 210°C.
[0028] In the present invention, the time of the second high pressure heat treatment is 10 to 15 hours.
[0029] In the present invention, after the second stage of high pressure heat treatment is completed, the material A can be obtained by optionally washing with water, washing with alcohol and drying.
[0030] In the present invention, in step 2, the auxiliary agent is at least one of sodium hydroxide and potassium hydroxide, preferably potassium hydroxide. The use of potassium hydroxide as an auxiliary agent can further synergistically optimize the physicochemical characteristics of starch-based hard carbon and further enhance its cycle performance.
[0031] Preferably, the weight ratio of material A to the auxiliary agent is 1: 1 to 5, preferably 1: 2 to 4. Under the preferred ratio, the physicochemical characteristics of starch-based hard carbon can be further optimized and its cycle performance can be further enhanced.
[0032] In the present invention, material A is pre-dispersed in water, and then an auxiliary agent is added for mixing and modification; or, the auxiliary agent is pre-dissolved in water, and then material A is added for mixing and modification. The present invention also shows that pre-dispersing material A in water, and then adding an auxiliary agent for mixing and modification can be combined with other processes to further synergize, further give more battery-compatible physical and chemical structures, and obtain better electrochemical performance.
[0033] In the present invention, the volume weight ratio of material A to water is 10 to 80 mL / g.
[0034] In the present invention, the temperature in the modification stage is 60 to 95°C, and may be 75 to 85°C.
[0035] In the present invention, the modification treatment time is 1 to 3 hours.
[0036] In the present invention, low-temperature carbonization is carried out in a protective atmosphere, which is at least one of nitrogen, an inert gas, a hydrogen-nitrogen mixed gas, and an inert gas-hydrogen mixed gas.
[0037] In the present invention, based on the combination of the above-mentioned processes, a hard carbon material having excellent capacity, tap density, fast charging and stability can be obtained under low temperature conditions.
[0038] In the present invention, the temperature of low-temperature carbonization is 800-900° C., preferably 840-860° C. Thanks to the combination of ingredients and processes, it can construct the physical and chemical characteristics of sodium-electricity adaptation at a relatively low temperature, and can further enhance its performance such as circulation in sodium-electricity.
[0039] In the present invention, the low-temperature carbonization time is 1 to 3 hours.
[0040] In the present invention, the starch-based hard carbon material is obtained by acid treatment, water washing, alcohol washing and drying after low-temperature carbonization.
[0041] The present invention also provides a starch-based hard carbon material obtained by the preparation method.
[0042] The preparation method of the present invention can give the prepared material more physical and chemical characteristics suitable for sodium batteries. When applied in sodium batteries, high energy density, high capacity and high rate stability can be obtained.
[0043] The present invention also includes the use of the starch-based hard carbon material of the present invention to prepare sodium ion batteries and their components based on conventional means and principles.
[0044] The present invention also provides a negative electrode material for a sodium ion battery, comprising a negative electrode active material, wherein the negative electrode active material contains the starch-based hard carbon material.
[0045] In the present invention, the negative electrode material, except for the starch-based hard carbon material of the present invention, other components and parts may be conventional.
[0046] For example, in the negative electrode active material, the content of the starch-based hard carbon material is above 50 wt.%, preferably above 80 wt.%; further, it may be the starch-based hard carbon material described in the present invention.
[0047] The negative electrode material of the present invention may also contain a binder and a conductive agent known in the industry;
[0048] In the negative electrode material of the present invention, the content of the negative electrode active material is 75-95wt.%.
[0049] The present invention also provides a negative electrode of a sodium ion battery, comprising a current collector and a negative electrode material composited on the surface of the current collector, wherein the negative electrode material is the negative electrode material comprising the starch-based hard carbon material described in the present invention.
[0050] In the negative electrode described in the present invention, in addition to the starch-based hard carbon material described in the present invention, other components such as the current collector and the like can be well-known.
[0051] The present invention also provides a sodium ion battery, which comprises the negative electrode described in the present invention.
[0052] The sodium ion battery of the present invention, in addition to comprising the starch-based hard carbon material of the present invention, other components and structures can be conventional. For example, it can be a solution-type sodium ion battery, which comprises a battery cell that is composited with a positive electrode, a diaphragm and a negative electrode, and an electrolyte that soaks the battery cell. In addition, it can also be a solid or semi-solid sodium ion battery, which comprises a battery cell that is composited with a positive electrode, a solid electrolyte and a negative electrode.
[0053] Beneficial Effects
[0054] The present invention uses the combined process to break up the association state between starch molecules, so that their surface can be solidified and pre-carbonized in a chaotic state, and then combined with auxiliary agent modification and low-temperature carbonization, which can effectively solve the problems of starch volume expansion and structural collapse when heated. In addition, its physical and chemical structure can be optimized to give it a sodium-electrically compatible physical and chemical structure, thereby obtaining starch-based hard carbon materials with excellent capacity, rate and fast charging performance at low temperatures. BRIEF DESCRIPTION OF THE DRAWINGS
[0055] Figure 1 is a SEM image of the hard carbon of Example 1;
[0056] Figure 2 The charge and discharge curve of the half-cell with the material of Example 1 as the electrode material;
[0057] Figure 3 is the SEM image of the carbon material in Example 2;
[0058] Figure 4 is the SEM image of the carbon material in Example 4;
[0059] Figure 5 is the SEM image of the carbon material in Comparative Example 1;
[0060] Figure 6 This is the SEM image of the carbon material in Comparative Example 2. DETAILED DESCRIPTION
[0061] The carbon material of the present invention can be used as a negative electrode material in secondary batteries, and is particularly suitable for sodium ion batteries.
[0062] In order to better illustrate the purpose, technical scheme and beneficial effects of the present invention, the present invention will be further described below in conjunction with the embodiments. It should be noted that the following implementation method is a further explanation of the present invention and should not be used as a limitation of the present invention.
[0063] Example 1
[0064] (1) 2 g of starch raw material (corn starch) was slowly added to 40 ml of deionized water with magnetic stirring, and the mixture was pre-heated in an open container, air atmosphere, normal pressure, temperature of 80° C., and stirring at 600 to 800 r / min for 30 min to obtain a product A system.
[0065] (2) The product A system was transferred to a 100 ml high-pressure reactor, and the container was sealed and heated to 200°C for high-pressure reaction for 12 hours. After the insulation was completed, the pressure was released, the solid-liquid separation was performed, and deionized water and ethanol were used for alternating washing 2 to 3 times, and then the product was dried in a vacuum drying oven at 80°C for 12 hours to obtain product B.
[0066] (3) Grind and weigh product B and disperse it in deionized water (liquid-to-solid ratio of 40-45 ml / g). Add an additive (KOH, where the mass ratio of product B to additive is 1:3) while magnetically stirring. Stir and modify at 80°C for 1 h. Place the stirred mixed solution in a drying oven at 100°C and dry it for 14-18 h.
[0067] (4) The dried solid was ground into powder and placed in a porcelain boat, which was wrapped with carbon cloth for protection and then placed in a tubular furnace. Argon gas was passed through the furnace for protection and carbonization was performed at 850 °C for 2 h at a heating rate of 1 °C / min. After carbonization, the powder was naturally cooled to room temperature.
[0068] (5) Prepare a sufficient amount of 1 M HCl solution, place the carbonized product in the HCl solution and stir it magnetically for 30 min to fully react and remove KOH, then filter it and repeatedly filter it with deionized water (the filtrate is neutral during washing) and ethanol, and vacuum dry it at 80 °C for 12 h to finally obtain product C (starch-based hard carbon material). Figure 1 This is the SEM image of product C. In the SEM characterization image, it can be clearly seen that there are many holes on the surface of the material. This structure can provide a storage place for sodium ions, so that the sodium ion battery can have a good capacity.
[0069] The prepared starch-based hard carbon material was mixed with conductive carbon black and PVDF in a mass ratio of 7:2:1, and an appropriate amount of NMP (N-methylpyrrolidone) was added to make a slurry. After stirring (6 h) sufficiently, it was evenly coated on a copper foil with a coater and dried in a vacuum at 60 °C for 12 h to obtain a surface density of 5 mg / cm 2 The negative electrode.
[0070] 1mol / LNaPF6 in ethylene glycol dimethyl ether (DME) solution was used as electrolyte, glass fiber as separator, and metal sodium sheet as counter electrode to assemble CR2025 button-type sodium ion battery in a glove box. Discharge was performed at room temperature at a current density of 1000mA / g, and then charge and discharge tests were performed at a current density of 50mA / g for 100 cycles, with a test voltage range of 0.01V to 2.50V.
[0071] The cycle performance of the battery is Figure 2 As shown in Table 1, the initial discharge specific capacity is 255.6 mAh / g, and the capacity retention rate after 100 cycles is 93.39%.
[0072] Example 2
[0073] Compared with Example 1, the only difference is that in step 3, KOH is pre-dissolved in deionized water and then product B is slowly added. The remaining operating steps are consistent with those of Example 1, and the obtained material is experimented with the same method as in the example.
[0074] Example 3
[0075] Compared with Example 1, the only difference is that in step 4, the carbonization temperature is changed to 750°C, the carbonization reaction time is 2h, the heating rate in the carbonization stage is 2°C / min, and the remaining operating steps are consistent with the steps in Example 1, and the obtained material is experimented with the same method as in the example.
[0076] Example 4
[0077] Compared with Example 1, the only difference is that in step 4, the carbonization temperature is changed to 950°C, the carbonization reaction time is 2h, the heating rate in the carbonization stage is 2°C / min, and the remaining operating steps are consistent with the steps in Example 1, and the obtained material is experimented with the same method as in the example.
[0078] Example 5
[0079] Compared with Example 1, the only difference is that in step 3, the amount of KOH is changed so that its weight is twice the weight of product B. The remaining operation steps are consistent with those of Example 1, and the obtained material is tested by the same method as in Example.
[0080] Example 6
[0081] Compared with Example 1, the only difference is that in step 3, the amount of KOH is changed to make its weight 4 times the weight of product B. The remaining operation steps are consistent with those of Example 1, and the obtained material is experimented with the same method as in Example.
[0082] Example 7
[0083] Compared with Example 1, the only difference is that in step 3, the auxiliary agent is sodium hydroxide, and the remaining operating steps are consistent with those of Example 1, and the obtained material is experimented with the same method as in the example.
[0084] Example 8
[0085] Compared with Example 1, the only difference is that the preparation process of product A in step 1 is changed. The different step (1) is: 2 g of starch raw material is pre-dispersed in 20 ml of solution A (4M CaCl2 aqueous solution), stirred for 30 to 40 minutes, and then added to 20 ml of deionized water for dispersion, and pre-heated in an open container, air atmosphere, normal pressure, temperature of 80°C, and stirring at 600 to 800 r / min for 30 minutes to obtain product A.
[0086] Other steps, operations and parameters are the same as in Example 1.
[0087] Comparative Example 1
[0088] Compared with Example 1, the only difference is that the normal pressure heat treatment in step 1 is not performed, but the starch and 40 mL of water are directly placed in a pressure autoclave at room temperature to perform step 2 and subsequent treatments.
[0089] Comparative Example 2
[0090] Compared with Example 1, the only difference is that in step 2, no high-pressure treatment is performed, that is, the product A of step 1 is dried and then used as product B to participate in step 3 and subsequent processing steps.
[0091] Comparative Example 3
[0092] Compared with Example 1, the only difference is that in step 3, KOH is not added, and other operations and parameters are the same as in Example 1.
[0093] Table 1
[0094]
[0095] It can be seen from Table 1 that, compared with the comparative example, the normal pressure-high pressure treatment process of the present invention can obtain excellent performance and improve the performance of the battery.
[0096] In addition, it can be seen from Examples 1 and 2 that pre-dispersing product B in water and then compounding with an additive can optimize the physical and chemical structure of the product and improve performance. It can be seen from Examples 1 / 3 to 4 that the scheme described in the present invention is different from the conventional heat treatment temperature of more than 1000°C, and can obtain better performance at a lower temperature.
[0097] In addition, it can be seen from Examples 1 and 7 that the use of potassium hydroxide as an auxiliary agent has better synergy with the solution of the present invention, which can further help to synergistically optimize the physical and chemical structure of hard carbon, so that it can exhibit better electrochemical performance.
[0098] Furthermore, it can be seen from Examples 1 and 8 that the preferred atmospheric pressure treatment process of the present invention can further facilitate the coordinated optimization of the physical and chemical structure of hard carbon, so that it can exhibit better electrochemical properties.
Claims
1. A method for preparing a starch-based hard carbon material, characterized in that the steps include: Step 1: The aqueous solution containing starch raw material is preliminarily subjected to a first stage of normal pressure heat treatment, and then subjected to a second stage of high pressure heat treatment in a closed container, and then separated to obtain material A; the temperature of the first stage of normal pressure heat treatment is above 50°C; the temperature of the second stage of high pressure heat treatment is above 100°C; Step 2: Material A and an auxiliary agent are slurried and modified with water to obtain material B; the auxiliary agent is an alkaline component or an acidic component; Step 3: Material B is subjected to low-temperature carbonization at a temperature of 750° C. to 950° C. to obtain the starch-based hard carbon material.
2. The method for preparing a starch-based hard carbon material according to claim 1, characterized in that: The starch raw material includes at least one of wheat starch, corn starch and potato starch; Preferably, the starch raw material is dispersed in water and mixed to obtain the aqueous solution containing the starch raw material; Preferably, the starch raw material is pre-dispersed in solution A and then dispersed in water to obtain the aqueous solution containing the starch raw material; the solution A is an aqueous solution in which at least one solute selected from calcium chloride, organic acid, chloroformaldehyde and alkali is dissolved; Preferably, the concentration of the solute in the solution A is 1 to 5 M, further 3 to 4 M; Preferably, in the aqueous solution containing starch raw materials, the liquid-to-solid ratio of water to starch raw materials is 5 to 50 ml / g.
3. The method for preparing a starch-based hard carbon material according to claim 1, characterized in that: The first stage of normal pressure heat treatment is carried out in an open container; Preferably, the atmosphere of the first stage of normal pressure heat treatment is air; Preferably, the temperature of the first stage of normal pressure heat treatment is 50-90°C; Preferably, the time of the first stage of normal pressure heat treatment is 0.5 to 1 h.
4. The method for preparing a starch-based hard carbon material according to claim 1, characterized in that: The system of the first stage of normal pressure heat treatment is placed in a sealed container and heated to perform the second stage of high pressure heat treatment; Preferably, the temperature of the second stage high pressure heat treatment is 150°C to 250°C; preferably 190°C to 210°C; Preferably, the second high pressure heat treatment lasts for 10 to 15 hours; Preferably, after the second stage of high pressure heat treatment is completed, the material A is obtained by optionally washing with water, washing with alcohol and drying.
5. The method for preparing a starch-based hard carbon material according to claim 1, characterized in that: In step 2, the auxiliary agent is at least one of sodium hydroxide and potassium hydroxide; Preferably, the weight ratio of material A to the auxiliary agent is 1:1-5; preferably 1:2-4; Preferably, material A is pre-dispersed in water, and then the auxiliary agent is added for mixing and modification; or, the auxiliary agent is pre-dissolved in water, and then material A is added for mixing and modification; Preferably, the volume weight ratio of material A to water is 10 to 80 mL / g; Preferably, the temperature in the modification stage is 60 to 95°C, and further can be 75 to 85°C; Preferably, the modification treatment time is 1 to 3 hours.
6. The method for preparing a starch-based hard carbon material according to claim 1, characterized in that: Low temperature carbonization is carried out in a protective atmosphere; Preferably, the protective atmosphere is at least one of nitrogen, inert gas, hydrogen-nitrogen mixture, and inert gas-hydrogen mixture; Preferably, the low temperature carbonization time is 1 to 3 hours; Preferably, the starch-based hard carbon material is obtained by acid treatment, water washing, alcohol washing and drying after low-temperature carbonization.
7. A starch-based hard carbon material obtained by the preparation method according to any one of claims 1 to 6.
8. A negative electrode material for a sodium ion battery, comprising a negative electrode active material, characterized in that: The negative electrode active material comprises the starch-based hard carbon material according to claim 7; Preferably, in the negative electrode active material, the content of the starch-based hard carbon material is above 50wt.%, preferably above 80wt.%; Preferably, the negative electrode material further comprises a binder and a conductive agent; Preferably, in the negative electrode material, the content of negative electrode active material is 75-95wt.%.
9. A negative electrode of a sodium ion battery, comprising a current collector and a negative electrode material composited on the surface thereof, characterized in that: The negative electrode material is the negative electrode material according to claim 8.
10. A sodium ion battery, characterized in that: The negative electrode according to claim 9 is included.
Citation Information
Patent Citations
Preparation method of high-performance porous carbon
CN105347342A
Preparation method of starch-based uniformly-dispersed activated carbon microsphere material and application thereof
CN105869912A
Preparation method and application of nitrogen-doped starch-based activated carbon microsphere material
CN105948045A
Hard carbon material as well as preparation method and application thereof
CN113800496A
Starch-based hard carbon negative electrode material and preparation method and application thereof
CN118439588A
